2022
DOI: 10.1021/acsmaterialsau.1c00068
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Production of Monodisperse Biopolymer Microcapsules for Latent Heat Storage

Abstract: Microencapsulation of phase change materials in a polymer shell is a promising technology to prevent them from leakage and to use them as a handleable powder state. However, the microencapsulation process is a timeconsuming process because the typical shell-forming step requires polymerization or evaporation of the solvent. In this study, we report a simple and rapid flow process to prepare monodisperse biocompatible cellulose acetate (CA) microcapsules encapsulating n-hexadecane (HD) for latent heat storage a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…The results showed that the microcapsules had an average latent heat of 87.5 J/g with a calculated encapsulation efficiency of 96.5%. 2022) [169] adopted the same approach to formulate microcapsules where a monodisperse biocompatible cellulose acetate (CA) constituted the shell materials and HD was used as the core material. Figure 23 shows the schematic representation of the microflow process used to produce the cellulose acetate-n-hexadecane microcapsules.…”
Section: Microfluidic Methodsmentioning
confidence: 99%
“…The results showed that the microcapsules had an average latent heat of 87.5 J/g with a calculated encapsulation efficiency of 96.5%. 2022) [169] adopted the same approach to formulate microcapsules where a monodisperse biocompatible cellulose acetate (CA) constituted the shell materials and HD was used as the core material. Figure 23 shows the schematic representation of the microflow process used to produce the cellulose acetate-n-hexadecane microcapsules.…”
Section: Microfluidic Methodsmentioning
confidence: 99%
“…The PCMs are first emulsified into droplets using the inner and middle fluids and then the droplets are encapsulated into the final product by the outer fluid (Figure 9d). Many materials have been explored for core/shell microencapsulated PCMs, including n ‐hexadecane/polyethylene glycol diacrylate (PEGDA), [ 133 ] water/trimethylolpropane ethoxylate triacrylate (ETPTA), [ 133 ] silicone/ n ‐hexadecyl bromide, [ 134 ] cellulose acetate/ n ‐hexadecane, [ 135 ] paraffin/isophorone diisocyanate and tetraethyenepentamine, [ 136 ] sodium acetate/acrylate, [ 137 ] n ‐tetradecane and n ‐hexadecane/silicon, [ 128 ] and n ‐heptadecane/hexanediol diacrylate polymer. [ 138 ] Further, nanoparticles can be incorporated into the microcapsules as exemplified by Lone et al who incorporated Fe 3 O 4 nanoparticles into the core of n ‐octadecane/polyurea microcapsules (Figure 9e).…”
Section: Energy Materials Fabricated By Microfluidic Techniquesmentioning
confidence: 99%
“…In this study, we developed a microfluidic process to prepare spherical particles with an interconnected open-porous structure using a bijel droplet as the template. A dispersed phase composed of a hydrophobic monomer, water, ethanol (cosolvent), photoinitiator, silica nanoparticles, and CTAB was used as the dispersed phase.…”
Section: Introductionmentioning
confidence: 99%